Prevalence of Gastrointestinal Helminthes in Students of Rivers State College of Health Science and Technology Port Harcourt - K. E. Okpara; C. U. Nyenke; H. O. Stanley; O. M. Immanuel (Archives of Current Research International, 2018)
This study was conducted to determine the prevalence of gastrointestinal helminthes among 347 students of Rivers State College of Health Science and Technology Port Harcourt aged 16-35 years. The study was carried out using both direct wet preparation and formal/ether concentration methods. Of the number sampled, 44 (12.7%) had various intestinal parasites with the occurrence of multiple parasitisms in some cases. The most common helminthes parasites isolated were Ascaris lumbricoides (40.9%); Hookworm (34.1%); Trichuris trichuria (18.2%); Strongyloides stercoralis (4.6%) and Schistosoma mansoni (2.3%). Students in the age group 16-20 had the highest infection rate (56.8%) followed by those of age group 21-26 (31.8%). Prevalence was higher in male (26.7%) than in female (8.8%) and was statistically significant (p<0.05). The level of co-infections was very low. The low prevalence of (12.7%) may be attributed to adequate health education, improved sanitary conditions, potable water supply, proper disposal of sewage and refuse and medical services, provided by the school. Nevertheless provision of adequate drainage system, roads and more modern toilet facilities and affordable medical services would further reduce susceptibility. Likewise, observation of personal hygiene, as well as routine examination and treatment, should be encouraged.